Produtividade e qualidade de grãos de canola em função da adubação nitrogenada e sulfatada - Lucas, Fabio Teixeira [UNESP]; Mendes Coutinho, Edson Luiz; Valente Paes, Jose Mauro; Barbosa, Jose Carlos (Universidade Estadual de Londrina (UEL), 2013)
The canola (Brassica napus, L.) cultivation was encouraged for grain and oil production at the 80's, and it is also considered a good option for crop rotation. The nitrogen is one of the most required nutrients by the plant to increase its production, while sulfur is essential to provide seed quality. Thus, the objective of this study was, at Cerrado region, evaluate the effects of nitrogen and sulfur fertilization at yield and contents of oil and crude protein in the grains. We also sought relate to grain yield the S content in the soil and concentrations of N and S in the diagnosis leaf. The experiment was conducted in Uberaba County, State of Minas Gerais, Brazil, in an Oxisol, utilizing the Hyola 401 hybrid. The treatments consisted in a factorial scheme 5 x 4 (five N rates: 0, 60, 100, 140 and 180 kg ha(-1) and; four S rates: 0, 15, 30 and 60 kg ha(-1)) in a randomized blocks design, with four replicates. The nitrogen and sulfur fertilization increased canola grain yield, without significantly alter contents of oil and crude protein. Rates higher than to 140 kg ha(-1) of N and 15 kg ha(-1) of S provided grain yield above 1100 kg ha(-1). Plots with yield higher than to 1000 kg ha(-1) presented foliar concentration of N above 52 g kg(-1). The highest S content was observed at the 0.15-0.30 m layer, proving the sulfate anion mobility. The lowest grain yield were observed when the S content in the soil at this layer were less than 4 mg dm(-3). The N concentrations in the diagnostic leaf and S-SO4-2 content in the 0.15-0.30 m layer correlated positively with crop yield.
Yield and quality of canola grains due to nitrogen and sulfur fertilization
Keywords: Brassica napus; Nitrogen; Sulfur; oil; Protein